Carrapato Boophilus microplus (Can. 1887) (Acari: ixodidae) resistente a ivermectina, moxidectina e doramectina. Rio Grande do Sul, Brasil - Joao Ricardo de Souza Martins (2006)
Trough preliminary field evaluation on naturally infested cattle it was identified one population of Boophilus microplus ticks which showed survival to a strategic control program with a macrocyclic lactone in the locality of São Gabriel, RS. This strain was maintained in laboratoryconditions and submitted to in vitro and stall tests. Immersion tests with adult females against ivermectin and moxidectin showed survival and egg laying in concentrations that range from 25 to 1000ppm for both active ingredients while in a susceptible tick population strain (Porto Alegre strain) there was 100% of mortality at 200 e 1000ppm. A first stall test showed variability in the daily efficacy, between 3 e 24 post treatment (p.t.), from 14.02% to 93.33%, against doramectin, from 30.25% to 89.00% against moxidectin and from 46.64% to 99.53% against ivermectin. In a second stall test, only with doramectin in comparison with a control group, average of efficacy was 64.15% between 1 and 23 days p.t., while the best efficacy was observed in the day 8 p.t.(82.68%). However, a third stall test against doramectin, showed variations in the efficacy between 10.73% and 74.22% between days 2 and 23 p.t. In adition, a comparative stall test with a susceptible reference strain (strain Porto Alegre) against doramectin, average of efficacybetween days 1 and 23 p.t. was 80.49% for the São Gabriel strain and 91.23% for the Porto Alegre strain. These results beyond showed a variability in the efficacy of some macrocyclic lactones, draw attention to the risks of decreasing acaricide efficiency with the intensive andsystematic use of a same active ingredient in the field, and, give emphasis to the needs of further in vitro tests in order to early detect arising of lactones macrocyclic resistant populations with minor cost and major confidence